Pengaruh Inovasi Dan Kreativitas Produk Terhadap Ketahanan Ekonomi Masyarakat Pada Industri Kerajinan Kapuk - Tessa Yuliani; Liz Izmuddin; Anne Putri (EKONOMIKA SYARIAH : Journal of Economic Studies, 2020)
This research is due to the problems in Jorong Batu Limbak related to the problem of making the cotton industry. For the people of Jorong Batu Limbak, the kapok handicraft industry is an industrial activity that must be developed so that people's economic resilience can be increased. This industry initially only processed cottonwood, but in its development there was a business making casual mattresses, dolls and others. The purpose of this study was to analyze the effect of the creativity of the kapok industrial product creativity on the economic resilience of the community in Jorong Batu Limbak. The research method used in this study is field research with a quantitative approach. The sample of this research is cotton entrepreneurs who innovate and creativity in the cotton industry. technical analysis used is multiple linear regression analysis. these findings reveal that Innovation and Creativity in the Kapok Industry in Jorong Batu Limbak have a significant influence on the economic resilience of the community as evidenced by the results of multiple linear regression Y = 12,962 + 0,22X1 + 0,628X2 + e. There is a positive influence between Product Innovation and product creativity on Community Economic Security, which is 51.2%